Kernel Based Algorithms for Mining Huge Data Sets Supervised, Semi-supervised, and Unsupervised Learning - Huang, Te-Ming.; Kecman, Vojislav; Kopriva, Ivica; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
"Kernel Based Algorithms for Mining Huge Data Sets" is the first book treating the fields of supervised, semi-supervised and unsupervised machine learning collectively. The book presents both the theory and the algorithms for mining huge data sets by using support vector machines (SVMs) in an iterative way. It demonstrates how kernel based SVMs can be used for dimensionality reduction (feature elimination) and shows the similarities and differences between the two most popular unsupervised techniques, the principal component analysis (PCA) and the independent component analysis (ICA). The book presents various examples, software, algorithmic solutions enabling the reader to develop their own codes for solving the problems. The book is accompanied by a website for downloading both data and software for huge data sets modeling in a supervised and semisupervised manner, as well as MATLAB based PCA and ICA routines for unsupervised learning. The book focuses on a broad range of machine learning algorithms and it is particularly aimed at students, scientists, and practicing researchers in bioinformatics (gene microarrays), text-categorization, numerals recognition, as well as in the images and audio signals de-mixing (blind source separation) areas.
Support Vector Machines in Classification and Regression $1 (BAn Introduction -- Iterative Single Data Algorithm for Kernel Machines from Huge Data Sets: Theory and Performance -- Feature Reduction with Support Vector Machines and Application in DNA Microarray Analysis -- Semi-supervised Learning and Applications -- Unsupervised Learning by Principal and Independent Component Analysis.s
Keywords: Computer science; Data mining; Artificial intelligence; Applied mathematics; Engineering mathematics; Computer Science; Data Mining and Knowledge Discovery; Appl.Mathematics/Computational Methods of Engineering; Artificial Intelligence (incl. Robotics).; Electronic books